Mode‐dependent intermediate variable‐based fault estimation for Markovian jump systems with multiple faults. (9th February 2021) - Kaviarasan, Boomipalagan; Kwon, Oh‐Min; Jin Park, Myeong; Sakthivel, Rathinasamy
Abstract: This article investigates the problem of mode‐dependent intermediate variable‐based fault estimation for Markovian jump systems subject to time‐varying delay, exogenous disturbance, process, and sensor faults. The advantages of the proposed design method are: (i) it estimates not only the unknown fault signals, but also the immeasurable states of the system; and (ii) it relaxes the observer matching condition that should be essential for most of the existing fault estimation strategies. In order to facilitate the analysis, the actual system is transformed into an augmented system by including the sensor fault as an auxiliary state. On the basis of which, the intermediate variable and the corresponding observers are established. Following this, two error dynamics are formulated in such a way that a new mode‐ and delay‐dependent boundedness criterion in the probability sense is developed in accordance with the traditional Lyapunov method. Then the theoretical results obtained are validated by using an example based on the F‐404 aircraft engine system. In addition, a comparative study is carried out in the deduced form of the actual system as a special case, where it is shown that the proposed method widens the delay interval compared with some of the recently existing works.